1985
DOI: 10.1002/bjs.1800720216
|View full text |Cite
|
Sign up to set email alerts
|

A study of the mechanical properties of fresh and preserved human femoral vein wall and valve cusps

Abstract: In the hope that some varieties of the post-phlebitic syndrome might be treated by implanting a preserved vein valve, studies have been made of the mechanical properties of vein valves and vein wall before and after preservation with glutaraldehyde. The ultimate tensile strength (breaking stress) and strain (extensibility) of strips of vein wall and valve leaflet were measured with a Nene tensiometer. The ultimate tensile strength of valve leaflet was found to be twice that of vein wall. Preservation in glutar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…It has been demonstrated that the endothelial cells in the venous valve sinus behave differently from the ones in avalvular areas and have the ability to stretch twice as much [62]. Similar measurements have not been made in lymphatic valve sinuses; however, it is known that they are devoid of smooth muscle cells [14], which is likely to enable more extensive stretching of the vessel wall in this region.…”
Section: Valve Morphogenesismentioning
confidence: 99%
“…It has been demonstrated that the endothelial cells in the venous valve sinus behave differently from the ones in avalvular areas and have the ability to stretch twice as much [62]. Similar measurements have not been made in lymphatic valve sinuses; however, it is known that they are devoid of smooth muscle cells [14], which is likely to enable more extensive stretching of the vessel wall in this region.…”
Section: Valve Morphogenesismentioning
confidence: 99%
“…However, as far we know, before our study [7] about the Young's modulus and the Poisson's coefficient, there has been no specific research into live venous tissue and its surroundings in humans. These physical parameters have already been calculated by other authors [8,9], but only for non live venous tissue.…”
Section: Introductionmentioning
confidence: 97%
“…In a previous study, preservation with buffered 1% glutaraldehyde did not significantly alter the mechanical properties related to the tensile strength of the vein wall (Ackroyd et al, 1985). To test for possible shrinkage due to chemical fixation and preservation in ethanol, we measured the inner circumference of three freshly-dissected veins prior to fixation, although unfixed veins could be more prone to measurement errors than fixed material owing to their soft-greasy consistency.…”
Section: Limitations Of This Studymentioning
confidence: 99%